Ekstaza i „nicość egzystencji”. O obrazach cielesności i jej barwach w prozie Brunona Schulza - Naróg , Aleksandra (Przestrzenie Teorii, 2020)
The aim of the following study is to investigate two creations of Jacob’s corporality evoking disgust in the short stories A Visitation, Birds and The Night of the Great Season from The Cinnamon Shops. My main field of interest is the connections between colours and form which surround Jacob’s body and evoke disgust. The context for the following study was the theoretical concepts of Mary Douglas, Julia Kristeva, Agata Bielik-Robson and Michał Paweł Markowski.